School-Based Education: An Opportunity to Promote Equitable Access to Sexual and Reproductive Health Knowledge - Walker, Ruth; Fields, Jessica; Gilbert, Jen; Leahy, Deana (Seminars in Reproductive Medicine, 2022)
All young people are entitled to knowledge and support that protects their sexual and reproductive health. School-based education is the most opportune setting for young people to have equitable access to sexual and reproductive health education. However, there is room for significant improvements in the provision of sexual and reproductive health education globally, and a range of barriers to be addressed. The Global Standards for Health Promoting Schools is a framework for governments, policy-makers, and schools to ensure that all students receive sexual and reproductive health education and support that promotes their sexual and reproductive health and overall health and well-being. The Global Standards for Health Promoting Schools acknowledges that school environments, partnerships, governance, policies, and resources are ultimately influenced by government resources and policy, and that advocacy and meaningful action across each standard is required.
Keywords: adolescents; sexual and reproductive health; education